MENINGKATKAN MINAT BELAJAR BIDANG BIMBINGAN PRIBADI DAN SOSIAL MATERI PENTINGNYA MENGATUR WAKTU DI SEKOLAH - M Yusuf (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2017)
Counseling services that use a lot of verbal, would be boring, otherwise the teaching and guidance counseling or services would be more interesting if the students excited to learn or happy because they feel interested and understand the material received the services. Thus the learning activities will be more effective. Phenomena mentioned above, encourage researcher to undertook an action research (action research) in Counseling services using information services in seventh A graders. The presentation result of the data research proved that the service information in Guidance Counseling services, could increase students' motivation in Guidance Counseling services that affect the interest of students in the seventh A graders of the the first state yunior high school Kalitengah Lamongan in following Counseling services.